Potential analgesic effect of Foshousan oil-loaded chitosan-alginate nanoparticles on the treatment of migraine - Chen, Yulong; Cheng, Qingzhou; Zeng, Shan; Lv, Site (Frontiers in Pharmacology, 2023)
Background: Migraine is a common neurovascular disorder with typical throbbing and unilateral headache, causing considerable healthcare burden on the global economy. This research aims to prepare chitosan-alginate (CS-AL) nanoparticles (NPs) containing Foshousan oil (FSSO) and investigate its potential therapeutic effects on the treatment of migraine.Methods: FSSO-loaded CS-AL NPs were prepared by using single emulsion solvent evaporation method. Lipopolysaccharide (LPS)-stimulated BV-2 cells and nitroglycerin (NTG)-induced migraine mice were further used to explore anti-migraine activities and potential mechanisms of this botanical drug.Results: FSSO-loaded CS-AL NPs (212.1 ± 5.2 nm, 45.1 ± 6.2 mV) had a well-defined spherical shape with prolonged drug release and good storage within 4 weeks. FSSO and FSSO-loaded CS-AL NPs (5, 10 and 15 μg/mL) showed anti-inflammatory activities in LPS-treated BV-2 cells via reducing the levels of pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6) and nitric oxide (NO), but elevating interleukin-10 (IL-10) expressions.Moreover, FSSO-loaded CS-AL NPs (52 and 104 mg/kg) raised pain thresholds against hot stimulus, and decreased acetic acid-induced writhing frequency and licking foot duration in NTG-induced migraine mice. Compared with the model group, calcitonin gene related peptide (CGRP) and NO levels were downregulated, but 5hydroxytryptamine (5-HT) and endothelin (ET) levels were enlarged along with rebalanced ET/NO ratio, as well as vasomotor dysfunction was alleviated by promoting cerebral blood flow (CBF) in the FSSO-loaded CS-AL NPs (104 mg/kg) group.neuroinflammation in LPS-stimulated BV-2 cells and regulating vasoactive substances in NTG-induced migraine mice. These findings suggest that the FSS formula may be exploited as new phytotherapy for treating migraine.